Non-Standard Work and Benefits: Has Anything Changed since the Wallace Report? - Zeytinoglu, Isik; Cooke, Gordon (Relations industrielles / Industrial Relations, 2005)
This paper examines whether there has been improvement in benefits coverage for non-standard workers since the Wallace Report in 1983. This study uses Statistics Canada’s Workplace and Employee Survey (WES) 1999 data. Results show significant differences in the receipt of benefits among non-standard workers, suggesting heterogeneity within this group of workers in terms of benefits coverage. Regular part-time and temporary full-time workers receive fewer benefits than regular full-time workers. Temporary part-time workers have significantly less likelihood of receiving benefits than the other three groups of workers. Overall, results show that since the Wallace Report findings, there has been little improvement in benefits coverage for non-standard workers, and they continue to be relatively disadvantaged in comparison to regular full-time workers.